2017
DOI: 10.17219/acem/62687
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic duct stones – a report of 16 cases

Abstract: Background. Pancreatolithiasis occurs in less than 1% of the general population and is mainly recognized in patients with chronic pancreatitis. Selection of the appropriate treatment method depends on the location, size and number of stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…At the same time, most scholars believe that although there are many factors affecting pancreatic fistula, including the preoperative nutritional status, pancreatic texture, and surgical experience of the surgeon, the MPD diameter is undoubtedly one of the most important factors [22]. The more obvious the degree of pancreatic duct dilatation is, the lower the risk of postoperative complications, especially pancreatic fistula, will be, which is an important reason for drainage or combined surgery requiring pancreatic duct expansion [22,23]. The results of this study showed that the incidence of pancreatic fistula was significantly decreased when the diameter of the pancreatic duct was greater than 7 mm or 8 mm, suggesting that 7 mm and 8 mm were the standard.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, most scholars believe that although there are many factors affecting pancreatic fistula, including the preoperative nutritional status, pancreatic texture, and surgical experience of the surgeon, the MPD diameter is undoubtedly one of the most important factors [22]. The more obvious the degree of pancreatic duct dilatation is, the lower the risk of postoperative complications, especially pancreatic fistula, will be, which is an important reason for drainage or combined surgery requiring pancreatic duct expansion [22,23]. The results of this study showed that the incidence of pancreatic fistula was significantly decreased when the diameter of the pancreatic duct was greater than 7 mm or 8 mm, suggesting that 7 mm and 8 mm were the standard.…”
Section: Discussionmentioning
confidence: 99%
“…Depending upon the stones’ type and number, they can be considered radio-opaque, radiolucent, or mixed, and also as single or multiple [ 2 , 3 ]. Importantly, there is a strong association with chronic pancreatitis (CP), which is present in 50–90% of these patients [ 4 ]. However, CP in the long term can be associated with a variety of complications affecting both the pancreas (pancreatic pseudocyst, pancreatitis and pancreatic adenocarcinoma) and the adjacent anatomical structures, causing biliary and duodenal obstruction [ 3 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Initial treatment for uncomplicated cases is usually conservative, and includes alcohol and smoking cessation, the use of supplements including pancreatic enzymes, proton pump inhibitors, and symptomatic treatment. Surgical and interventional procedures are reserved for the cases with CP resistant to conservative treatment and complications, which are quite common (increased intrapancreatic pressure, pseudocysts, fistulas or abscesses, stenosis of the duodenum and bile duct, calculus, vascular disorders and neoplasms) [5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%